APPLICATION OF CRIMINAL SANCTIONS IN CASES OF MANIPULATION OF DEMAND AND COLLECTION OF HEALTH SERVICES FEES FOR PATIENTS PARTICIPATING IN THE NATIONAL HEALTH INSURANCE PROGRAM - Hardy Hutahaean (Jurnal Hukum Khaira Ummah, 2022)
The aim of this study is to conduct studies and analyze the weaknesses of the application of criminal sanctions oncases of manipulation of requests and collection of health care costs for patients participating in the National Health Insurance Program so far and provide solutions. The research method used is a normative juridical approach and the type is descriptive qualitative. The data used in this study is secondary data, namely by examining theories, concepts, legal principles and legislation related to this research to be analyzed in order to obtain qualitative data. The conclusion of this study is that there is no formulation of lex specialist criminal sanctions for cases of manipulation of requests for health care costs for patients participating in the National Health Insurance Program. The punishment of the perpetrators of the act of manipulating the demand for fees requires various aspects, including the excesses of the punishment, both to the perpetrators and to the health service ecosystem for the Participants of the National Health Insurance Program. The role of Good Corporate Governance and Good Clinical Governance as a preventive effort in this case is also a very strategic matter.Keywords: National Health Insurance Program; Fraud; Law enforcement.